2013
DOI: 10.2527/jas.2012-6068
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance and carcass quality of immunocastrated and surgically castrated pigs from crossbreds from Duroc and Pietrain sires1

Abstract: In total, 240 pigs were used to compare growth performance and carcass quality traits of immunocastrated males (ICM), surgically castrated males (SCM), and intact females (IF) of crossbreds from Large White × Landrace females and Duroc (DU) or Pietrain (PI) sires destined to the dry-cured industry. Between the 2 Improvac injections (87 and 137 d of age), ICM and IF had less ADG than SCM (P < 0.01). Also, ICM ate less feed than IF and both less than SCM (2.33, 2.55, and 2.77 kg/d; respectively; P < 0.001) and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
19
3
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 42 publications
12
19
3
5
Order By: Relevance
“…The BF depth at P2 site (65 mm off the midline over the last rib) was measured in all pigs using a portable real-time ultrasound scanner (Model ACO37L, Vetko Plus, Noveko, Quebec, Canada) as described by Morales et al (2011) at 125, 146 and 159 days of age (64, 85 and 98 days on trial) with the last measurement corresponding to the evening before slaughter. Images were frozen and recorded using the software provided by the ultrasound equipment.…”
Section: Carcass Qualitymentioning
confidence: 99%
“…The BF depth at P2 site (65 mm off the midline over the last rib) was measured in all pigs using a portable real-time ultrasound scanner (Model ACO37L, Vetko Plus, Noveko, Quebec, Canada) as described by Morales et al (2011) at 125, 146 and 159 days of age (64, 85 and 98 days on trial) with the last measurement corresponding to the evening before slaughter. Images were frozen and recorded using the software provided by the ultrasound equipment.…”
Section: Carcass Qualitymentioning
confidence: 99%
“…Com relação aos fatores hormonais, estudos vêm demonstrando que a testosterona é responsável pelo aumento da síntese proteica, o que confere a suínos machos não castrados melhor deposição de carne magra que machos castrados (Font-i-Furnols et al, 2012, Morales et al, 2013.…”
Section: Pubvetunclassified
“…Este fato foi confirmado em uma série de estudos, que demonstraram pouca ou nenhuma diferença no ganho médio e eficiência alimentar entre machos imunocastrados e machos inteiros, entre a primeira e segunda dose (Fàbrega et al, 2010, Batorek et al, 2012a, Morales et al, 2013.…”
Section: Alternativas Para Explorar a Síntese Proteica Em Suínos Machosunclassified
See 1 more Smart Citation
“…According to Carroll et al (2005), castration is stressful independent of age; however, the stress associated with handling seems to increase with age. Morales et al (2013) when comparing immunocastrated males (IC), surgically castrated males (PC) and intact females (IF), observed that IC showed greater ADG for the entire period studied (d 87 to 164) and less ADFI, resulting in improved feed efficiency when compared to PC and IF.…”
Section: Animal Performancementioning
confidence: 99%